1999
DOI: 10.1002/(sici)1096-9063(199909)55:9<955::aid-ps29>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis and hydrolysis of rimsulfuron

Abstract: The degradation in the liquid phase of rimsulfuron and its commercial 250 g kg À1 WG formulation (Titus 1 ) was investigated. Photolysis reactions were carried out at 25°C by a highpressure mercury arc (Hg-UV) and a solar simulator (Suntest), while the hydrolysis rate was determined by keeping aqueous buffered samples in the dark. The effects of solvent and water pH on reaction kinetics were studied, and the results compared to literature data. Photoreactions of the commercial product in organic solvents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…Hydrolysis and photolysis reactions occurred simultaneously during irradiation. Therefore, the photolysis contribution was calculated by adding the quantity ( C 0 − C ) dark , which dissipated in a certain time in the dark, to the remaining ( C ) light concentration detected in the irradiated solution at the same time, where C 0 represents the initial concentration of the herbicide and C represents the concentration at a certain time 10. Data were processed using MassLynx (version 3.4) software.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrolysis and photolysis reactions occurred simultaneously during irradiation. Therefore, the photolysis contribution was calculated by adding the quantity ( C 0 − C ) dark , which dissipated in a certain time in the dark, to the remaining ( C ) light concentration detected in the irradiated solution at the same time, where C 0 represents the initial concentration of the herbicide and C represents the concentration at a certain time 10. Data were processed using MassLynx (version 3.4) software.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfonylurea herbicides provide good crop selectivity; with very low application rates and favorable environmental and toxicological properties (Beyer et al, 1988;Scrano et al, 1999;Sarmah & Sabadie, 2002). Sulfonylurea herbicides are characterized by their low vapor pressure, high water solubility (200 g L À1 for metsulfuron-methyl), and high phytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The photolysis of sulfonylurea herbicides under artificial radiation sources is known to follow first-order kinetics (Beyer et al, 1988;Pusino et al, 1999;Scrano et al, 1999). However, mass spectrometry studies of the photolysis under natural sunlight have been limited and not widely reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the photochemical behavior of sulfonylurea herbicides depends on the pH (Vulliet et al, 2004). Scrano et al (1999) reported the whole reaction (photolysis + hydrolysis) under sunlight is faster in acidic and alkaline conditions than in neutral solutions. The pH value was in neutral range of 7.4 and 7.6 for treatment and control in this study.…”
Section: Resultsmentioning
confidence: 99%